Expression of stable reference genes and SPINDLY gene in response to gibberellic acid application at different stages of grapevine development - Upadhyay, A.; Jogaiah, S.; Maske, S. R.; Kadoo, Narendra Y.; Gupta, V. S. (Biologia Plantarum, 2015)
Gibberellic acid (GA(3)) is widely used at different stages of berry development, and to understand the molecular mechanism of its action requires identification of stable reference genes. We sprayed grapevine (Vitis vinifera L.) cv. Thompson Seedless with GA(3) at rachis stage for rachis elongation, at flower cluster stage for flower thinning, and at 3 - 4 mm berry stage for berry elongation. Tissue samples were collected at different time points after GA(3) application. The expression of 10 candidate reference genes was analyzed using 4 different algorithms to assess their suitability for real time-PCR data normalization. Based on the overall ranking, PP2A, Sutra, and SAND were identified as the most stably expressed genes across all samples. With regard to different stages, tubulin, EF1 alpha, and UBC were the most stable genes during rachis elongation; PP2A, SAND, and Sutra were the most suitable at the flower cluster and berry stages. The expression of GA signaling gene SPINDLY (VvSpy) was analyzed to validate the stable reference genes. After the GA(3) application, the expression of VvSpy was reduced at the rachis stage but did not change at the flower cluster and berry stages. The expression profile of VvSpy was comparable when two or three reference genes were used for data normalization.
Keywords: developmental stages; Vitis vinifera